(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The new circumstances of life due to the proclamation of the COVID 19 virus pandemic have caused numerous changes both in general people’s lives and in consumption. The aim of this paper is to identify changes in the degree of consumer ethnocentrism when choosing products during COVID 19 virus pandemic, compared to the period before its occurrence. In addition, differences in consumer preferences for certain product and service categories of domestic producers before and during the pandemic were analyzed. A paired t test is used for this purpose. By analyzing the primary data collected from 176 respondents, higher level of consumer ethnocentrism is confirmed in period during pandemic, specially when it comes to choice of medical products of domestic origin. Theoretical implications of the paper relate to expanding current knowledge about the effects of the COVID 19 pandemic on consumer behavior, while managerial implications include the possibility of using scientific results in formulating and implementing appropriate strategies to encourage domestic economic development by strengthening consumer ethnocentrism in the market.